Fast, simple and reliable triglyceride composition analysis of milk fat for discrimination of cheese origin and adulteration detection. (September 2019) - Petronijevic, R B; Trbovic, D; Milicevic, D
Abstract: Optimization of a novel high performance liquid chromatography with refractive index detection method, together with accelerated solvent extraction for determining the triglyceride composition of lipids to enable rapid discrimination of goat and cow cheeses is presented. The method was applied to determine adulteration of goat and cow cheeses with vegetable oils/fats, to distinguish cheese analogues from natural cheeses, and to determine the amounts of palm fat added to cheese. Principal component analysis of triglycerides grouped by equivalent carbon number was used for confirmation of cheeses' animal origins. A total of 130 cheeses or cheese analogues were included in this study. The method was calibrated in the range of 0 to 50 % palm fat in milk fat, with recovery values being from 46.50 % to 108.48 %. The content of palm fat found in adulterated cheese was from 10 to 16 %, and 5 to 10 % in cow and goat cheeses, respectively. Due to the rapidity of the method, employment of relatively inexpensive equipment and the reliability of the results, the method proved to be suitable for analytical laboratories that are required to process large numbers of cheese samples in a short time.